A Nutraceutical Product Based on a Mixture of Algae and Extra Virgin Olive Oils and Olive Leaf Extract Attenuates Sepsis-Induced Cardiovascular and Muscle Alterations in Rats - González-Hedström, Daniel; Moreno-Rupérez, Álvaro; de la Fuente-Fernández, María; de la Fuente-Muñoz, Mario; Román-Carmena, Marta; Amor, Sara; García-Villalón, Ángel Luís; López-Calderón, Asunción; Isabel Martín, Ana; Priego, Teresa; Granado, Miriam (Frontiers in Nutrition, 2022)
Nutraceuticals are products of natural origin widely used for the treatment and/or prevention of some chronic diseases that are highly prevalent in Western countries, such as obesity or type II diabetes, among others. However, its possible use in the prevention of acute diseases that can put life at risk has been poorly studied. Sepsis is an acute condition that causes cardiovascular and skeletal muscle damage due to a systemic inflammatory state. The aim of this work was to evaluate the possible beneficial effect of a new nutraceutical based on a mixture of algae oil (AO) and extra virgin olive oil (EVOO) supplemented with an olive leaf extract (OLE) in the prevention of cardiovascular alterations and skeletal muscle disorders induced by sepsis in rats. For this purpose, male Wistar rats were treated with the nutraceutical or with water p.o. for 3 weeks and after the treatment they were injected with 1mg/kg LPS twice (12 and 4 h before sacrifice). Pretreatment with the nutraceutical prevented the LPS-induced decrease in cardiac contractility before and after the hearts were subjected to ischemia-reperfusion. At the vascular level, supplementation with the nutraceutical did not prevent hypotension in septic animals, but it attenuated endothelial dysfunction and the increased response of aortic rings to the vasoconstrictors norepinephrine and angiotensin-II induced by LPS. The beneficial effects on cardiovascular function were associated with an increased expression of the antioxidant enzymes SOD-1 and GSR in cardiac tissue and SOD-1 and Alox-5 in arterial tissue. In skeletal muscle, nutraceutical pretreatment prevented LPS-induced muscle proteolysis and autophagy and significantly increased protein synthesis as demonstrated by decreased expression of MURF-1, atrogin-1, LC3b and increased MCH-I and MCH -IIa in gastrocnemius muscle. These effects were associated with a decrease in the expression of TNFα, HDAC4 and myogenin. In conclusion, treatment with a new nutraceutical based on a mixture of AO and EVOO supplemented with OLE is useful to prevent cardiovascular and muscular changes induced by sepsis in rats. Thus, supplementation with this nutraceutical may constitute an interesting strategy to reduce the severity and mortality risk in septic patients.